Resting (Tonic) Blood Pressure Is Associated With Sensitivity to Imagined and Acute Experiences of Social Pain: Evidence From Three Studies - Inagaki, Tristen K.; Gianaros, Peter J. (Psychological Science, 2022)
Social pain is a common experience that has potent implications for health. However, individuals differ in their sensitivity to social pain. Recent evidence suggests that sensitivity to social pain varies according to a biological factor that modulates sensitivity to physical pain: resting (tonic) blood pressure. The current studies extended this evidence by testing whether blood pressure relates to sensitivity to imagined (Study 1: N = 762, 51% female adults) and acute (Study 2, preregistered: N = 204, 57% female adults) experiences of social pain and whether associations extend to general emotional responding (Studies 1–3; Study 3: N = 162, 59% female adults). In line with prior evidence, results showed that higher resting blood pressure was associated with lower sensitivity to social pain. Moreover, associations regarding blood pressure and sensitivity to social pain did not appear to be explained by individual differences in general emotional responding. Findings appear to be compatible with the interpretation that social and physical pain share similar cardiovascular correlates and may be modulated by convergent interoceptive pathways.